An analysis of the Skills Acquisition Trainer for badminton program: Exploring the effectiveness of visual based training in sport - Huynh, M. V.; Bedford, A. (International Journal of Computer Science in Sport, 2011)
This study examined the use of the Skills Acquistion Trainer for Badminton (SATB) software as a visual based training (VBT) method for a group of 41 participants. Using this program, we identified the athlete's skill level and awareness, and attempted to improve their overall in-game performance and decision making skills. Three different types of analyses were conducted on the SATB over the ten weeks of experimentation. Firstly, discriminant analysis was used to assess the accuracy that the SATB program had in classifying participants into the correct skill level groups. Secondly, a repeated measures ANOVA was carried out to examine the changes in score over the ten weeks of experimentation. Finally, a Pearson's correlation was carried out to examine the linear dependence between SATB variables and motor fitness constructs. The results from this study revealed three main findings: (1) the program was successful in predicting group membership among badminton players, with an accuracy of 87.8%, (2) players demonstrated a significant improvement on anticipatory techniques and (3) skill level was significantly correlated with SATB constructs. Overall, this study demonstrates the effectiveness of VBT in sport, and discusses the implications of perceptual skill acquisition and development.